2007
DOI: 10.1113/jphysiol.2007.145185
|View full text |Cite
|
Sign up to set email alerts
|

pH dependence of melanoma cell migration: protons extruded by NHE1 dominate protons of the bulk solution

Abstract: Migration and morphology of human melanoma cells (MV3) depend on extracellular pH (pHe) and the activity of the Na+/H+ exchanger NHE1. To distinguish effects of NHE1 activity per se from effects of pHe we compared an NHE1-deficient mutant with rescued and wild-type cells. Time lapse video microscopy was used to investigate migratory and morphological effects caused by pHe and NHE1 activity, and a membrane-bound fluorescein conjugate was employed for ratiometric pH measurements at the outer leaflet of the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
164
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(171 citation statements)
references
References 39 publications
6
164
0
1
Order By: Relevance
“…This re sults from the ab nor mal meta bolic ac tiv ity of can cer cells, in clud ing in creased gly colytic flux and lac tic acid re lease [150]; car bon diox ide pro duc tion by the TCA cy cle and the pen tose phos phate path way (PPP) [151][152][153][154]; over ex pres sion or up reg u lated ac tiv ity of car bonic an hy drases [155,156] and pro ton trans porters [156]; and de creased pro ton clear ance in the tu mor en vi ron ment [157]. Pro ton ex tru sion and ex tra cel lu lar acid i fi ca tion make ad her ent junc tions lose [158], stim u late mi gra tion and cy toskele ton re or ga ni za tion [159][160][161][162][163], and pro mote the ex pres sion [164,165], re lease [166,167] and ac tiv ity [167,168] of pro teases that de grade the ex tra cel lu lar ma trix. Hence, acidic prim ing was shown to be suf fi cient to in crease lung col o niza tion fol low ing sar coma and melanoma tu mor cell in jec tion in the tail vein of mice [163,167,169,170].…”
Section: Metabolic Contribution To Cancer Metastasismentioning
confidence: 99%
“…This re sults from the ab nor mal meta bolic ac tiv ity of can cer cells, in clud ing in creased gly colytic flux and lac tic acid re lease [150]; car bon diox ide pro duc tion by the TCA cy cle and the pen tose phos phate path way (PPP) [151][152][153][154]; over ex pres sion or up reg u lated ac tiv ity of car bonic an hy drases [155,156] and pro ton trans porters [156]; and de creased pro ton clear ance in the tu mor en vi ron ment [157]. Pro ton ex tru sion and ex tra cel lu lar acid i fi ca tion make ad her ent junc tions lose [158], stim u late mi gra tion and cy toskele ton re or ga ni za tion [159][160][161][162][163], and pro mote the ex pres sion [164,165], re lease [166,167] and ac tiv ity [167,168] of pro teases that de grade the ex tra cel lu lar ma trix. Hence, acidic prim ing was shown to be suf fi cient to in crease lung col o niza tion fol low ing sar coma and melanoma tu mor cell in jec tion in the tail vein of mice [163,167,169,170].…”
Section: Metabolic Contribution To Cancer Metastasismentioning
confidence: 99%
“…Time-lapse and immunofluorescence microscopy Time-lapse microscopy experiments were essentially performed as described previously (Stu¨we et al, 2007). A detailed description of time-lapse microscopy experiments is available in the Supplementary Information.…”
Section: Matrigel Invasion Assaymentioning
confidence: 99%
“…It is reported that the asymmetrical expression and activation of NHE1 in cells generates a local intracellular pH gradient and thus induces or at least supports the rearrangement of the cytoskeleton by affecting cofilin, an actin-binding protein that increases the recycling of actin monomers [1] . While a great deal of effort has been focused on the involvement of NHE1 in cell migration and polarity [33][34][35][36] , two studies have demonstrated that protons, released via C. elegans intestinal NHE PBO-4 (also known as NHX-7, the ortholog of mammalian NHE1), act on a proton-gated cation channel (comprised of PBO-5 and PBO-6 subunits) located in the adjacent muscle cells to induce contraction during the defecation cycle [5,6] . These studies provided characterized [37] .…”
Section: Vacuolar Type H + -Atpases (V-atpases) Vacuolarmentioning
confidence: 99%